Politics without boarders : Philippine politics and governance - Mendoza, Diana J.; Melegrito, Ma. Lourdes F. (Quezon City : Phoenix Publishing House, 2016)
Politics Without Borders: Philippine Politics and Governance offers an informed introduction to Philippine politics and governance and a balanced treatment of some of the key debates, issues, and disagreements that characterize the country's politics and governance. The textbook does not only equip the students with knowledge and skills but also develops in them a value-critical stance on existing rules, policies, institutions, and processes in the Philippines and an appreciation of the democratic political order in the country. It also encourages the students to be aware of the complexities and implications of democratic life in the Philippines. It also challenges them to participate actively in, as well as contribute to the deepening of the country's democracy.
Chapter 1. Politics and the study of politics -- Chapter 2. History of Democratic politics in the Philippines -- Chapter 3. Institutions and processes of government -- Chapter 4. Decentralization and local governance -- Chapter 5. State-society interactions -- Chapter 6. Citizenship-n-practice.
Includes bibliographical references.
Keywords: PHILIPPINES -- POLITICS AND GOVERNANCE